Step-by-step explanation:
remember that f(x) stand for y in the coordinate grid.
so, we actually have
y = sqrt(2x - 6)
in the inverse function we try to camcorder the original x out of a given y result.
for that function we need to transform the y = ... function into a x = ... form. and then we simply rename x to y and vice versa to create a regular function.
y = sqrt(2x - 6)
let's square both sides to get rid of the square root.
y² = 2x - 6
2x = y² + 6
x = y²/2 + 3
now renaming the variables, and the inverse function is
y = f-1(x) = x²/2 + 3